Satellite and terrestrial radio positioning techniques a signal processing perspective - Luise, Marco; Falletti, Emanuela (Academic, 2012)
Written and edited by leading experts in the field, with contributors belonging to the European Commission's FP7 Network of Excellence NEWCOM++ Applications to a wide range of fields, including sensor networks, emergency services, military use, location-based billing, location-based advertising, intelligent transportation, and leisure Location-aware personal devices and location-based services have become ever more prominent in the past few years, thanks to the significant advances in position location technology. Sensor networks, geographic information, emergency services, location management, location-based billing, location-based advertising, intelligent transportation, and leisure applications are just some of the potential applications that can be enabled by these techniques. Increasingly, satellite and terrestrial positioning techniques are being combined for maximum performance; to produce the next wave of location-based devices and services, engineers need to combine both components. This book is the first to present a holistic view, covering all aspects of positioning: both terrestrial and satellite, both theory and practice, both performance bounds and signal processing techniques. It will provide a valuable resource for product developers and R&D engineers, allowing them to improve existing location techniques and develop future approaches for new systems. Combines satellite and terrestrial positioning techniques, using a signal processing approach. Discusses the applicability of developed techniques to emerging standards, such as LTE Advanced or WiMAX II, through the issue of ranging measurement with multicarrier signals. Contains quantitative performance results for ranging, positioning, and tracking for various systems.